Public reporting on pharmaceutical industry-led access programs: alignment with the WHO medicine programs evaluation checklist - Chukwuemeka A. Umeh; Peter C. Rockers; Richard Laing; Ovi Wagh; Veronika J. Wirtz (Taylor & Francis Group, 2020)
Background There has been increased demand for greater public accountability and transparency of private sector-led global health partnership programs. This study critically reviews and pilot tests the World Health Organization (WHO) medicine program checklist as a framework for public reporting and assessing of programs. Methods We reviewed each question on the WHO checklist for clarity and usability. Next, we pilot tested the subset of checklist questions focused on program assessment. We extracted and analyzed publicly available information on one randomly selected program from each of the 20 largest research-based biopharmaceutical companies. For each program, we assessed whether publicly available information allowed for an assessment of each relevant question in the checklist. Results Checklist questions fit in four main categories: [1] national health and development plans, needs, capacity, laws and policies; [2] financial, performance, and public accountability; [3] risk management and mitigation strategies; and [4] long-term sustainability. Nearly all (21 of 22) questions in the checklist require information best provided by companies; one question requires information best provided by governments. Programs frequently reported on the public health needs of their programs (100%), program objectives and activities (100%) and the actual or expected program outputs (95%). There was less information on program alignment with country plans and capacity (50%), detailed program monitoring and evaluation plan (20%), risks mitigation strategies (5%), program needs assessment (5%), and additional resources required from or contributed by government (0%). Conclusion The WHO checklist of key considerations for evaluating proposals for access to medicine programs could be a useful framework for public reporting of program information as most of checklist questions ask for data that should be available to those leading the program. Further revisions of the WHO checklist will help refine it to improve clarity and content validity.